Priority issues of methodological and psychological provisions for combatants' training process - Vasilyev, G. F.; Tiunova, O. V.; Novikov, A. A. (Theory and Practice of Physical Culture, 2017)
Abstract: It is a common knowledge that an individual development in any sector and field of activity requires the relevant accumulated experience and applied technologies being regularly revised and revaluated and the relevant professional discussions being encouraged. The article overviews the priority vectors of the theoretical and practical improvements in the training systems applied by martial artists of different skill levels. The study identified a few bottlenecks in the modern sport development process and offered some practical solutions based on the long-term personal experiences of the authors in the theoretical and practical training and mental conditioning domains. The article was primarily designed to encourage a productive discussion in the professional sport communities and at the same time support the relevant research and coaching activities.